2020
DOI: 10.1016/j.tics.2020.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Pupil Size as a Window on Neural Substrates of Cognition

Abstract: Pupil modulations provide a non-invasive window onto how the brain performs many cognitive tasks. Here we review recent work that has begun to identify specific neural underpinnings of these cognitively driven pupil signals, including key roles for: 1) the superior colliculus (SC), which mediates responses to salient stimuli that evoke orienting responses; and 2) the locus coeruleus (LC), the source of a major neuromodulator (norepinephrine) that mediates arousal and cognition. We discuss how these findings ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
486
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 446 publications
(510 citation statements)
references
References 186 publications
(216 reference statements)
19
486
5
Order By: Relevance
“…As described above, decades of research have shown that eye metrics are related to task performance in a variety of contexts [8][9][10][11][12][13]. Heightened levels of arousal have been associated with a large pupil.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As described above, decades of research have shown that eye metrics are related to task performance in a variety of contexts [8][9][10][11][12][13]. Heightened levels of arousal have been associated with a large pupil.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of work has shown that arousal is associated with changes in the action of the eyes, be it when they are relatively stable or when they move. For example, increases in arousal are typically accompanied by increases in pupil size and saccade velocity, and concomitant decreases in microsaccade rate and reaction time [8][9][10][11][12][13][30][31][32][33][38][39][40][41]. Given that arousal is a domain-general phenomenon, one might expect a similar pattern to emerge on different behavioral tasks.…”
Section: Correlations Between the Eye Metrics Over Timementioning
confidence: 99%
See 3 more Smart Citations